Sulla libertà e il potere - Di Salvatore, Graziella (SocietàMutamentoPolitica, 2012)
The critical note compares the philosophical-political texts of Laura Bazzicalupo (2011), Heroes of the liberty. Histories of revolt against the power, The Mill, Bologna, and of Giacomo Marramao (2011), Against the power, Bompiani, Milano. Reflecting on the dynamics and the problems more purely of order “practical” that the two authors develop in their jobs discussing the concepts of liberty and power had and evolved in the space and in the time of the western civilization, the job intend to analyze the match liberty-power beginning from some topical questions, to them tie: what are the liberty and the power and which are their presuppositions? Is it possible in last to think the two concepts without the conflicting classical dynamics of the modernity but in direct correlation among them?